2013
DOI: 10.1590/s0101-20612013005000021
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and microbiological evaluation of corrientes artisanal cheese during ripening

Abstract: The aim of this study was to evaluate some physical and chemical parameters (total solids, pH, acidity, fat, acid degree value of fat, salt, protein and nitrogen fractions) and their effects on the beneficial (lactic acid bacteria: LAB) and undesirable microbial populations (coliforms, Escherichia coli, Staphylococcus aureus, moulds, and yeast) during ripening of Artisanal Corrientes Cheese, an Argentinian cow's milk variety, to determine whether a longer ripening period than usual improve its hygienic-sanitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
4
16
1
5
Order By: Relevance
“…The CA and CB showed significant increase (p < 0.05) in acidity during the ripening, similar to other studies (Bontinis et al, 2008;Vasek et al, 2013). At 0 and 60 days of ripening, CA exhibited lower acidity values than CB.…”
Section: Physicochemical Analysissupporting
confidence: 89%
“…The CA and CB showed significant increase (p < 0.05) in acidity during the ripening, similar to other studies (Bontinis et al, 2008;Vasek et al, 2013). At 0 and 60 days of ripening, CA exhibited lower acidity values than CB.…”
Section: Physicochemical Analysissupporting
confidence: 89%
“…Vasek et al (2013) and Longaray et al (2012) reported acidity values similar to those found in our study (0.75% and 0.23 to 0.89% respectively), in artisanal cheeses from Corrientes, Argentina, and in Serrano cheese (a traditional cheese from southern Brazil), emphasizing that this acidity level is normal in fresh cheeses or those with a short maturation period. González (2010) characterized fresh cheese made with unpasteurized milk (made according to artisanal methods in the municipality of Minatitlán, Veracruz, Mexico), and reported similar results to our study with maximum acidity values of 0.846, with lactic acid as the main acid.…”
Section: Resultssupporting
confidence: 91%
“…The microbial variability was also related to the age of the cheese samples. Both of these facts are supported by studies on other varieties of artisan cheeses in general (Vasek et al ; Irlinger et al ; O'Sullivan et al ). Cheese produced in farms from nonpasteurised milk (cow/sheep) and without a starter culture showed significantly higher microbial diversity than cheeses produced in HACCP dairies.…”
Section: Discussionmentioning
confidence: 57%